Subarachnoid hemorrhage that electrocardiographically mimics acute coronary syndrome: a case report - Erkan Köklü; İsa Öner Yüksel; Nermin Bayar; Selçuk Küçükseymen; Şakir Arslan (Türk Kardiyoloji Derneği Arşivi, 2015)
Electrocardiography alterations and cardiac enzyme elevation have been reported in patients with cerebrovascular events in various articles. This case reports a case of syncope with an electrocardiography of atrioventricular complete block and extensive ST segment elevation. However, it was finally diagnosed as subarachnoid hemorrhage. To the best of our knowledge, this patient is the first case of subarachnoid hemorrhage mimicking ST elevation myocardial infarction with atrioventricular complete block.